2014
DOI: 10.1111/febs.12710
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of chicken cytochrome P450 2D49 basal expression by CCAAT/enhancer‐binding protein α and hepatocyte nuclear factor 4α

Abstract: Chicken cytochrome P450 (CYP)2D49 is structurally and functionally related to human CYP2D6, which is an important drug-metabolizing enzyme. To date, little is known about the transcriptional regulation of this cytochrome. Through deletion analysis of the CYP2D49 promoter, we identified two putative degenerate CCAAT/enhancer-binding protein (C/ EBP)-binding sites and an imperfect DR1 element (the site contains direct repeats of the hexamer AGGTCA separated by a one-nucleotide spacer motif) within regions -296/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Our analysis highlighted the importance of SRF in stomach protection. The activated transcription factor CEBPA regulates proteins related to metabolism and detoxification, especially cytochrome P450 26 , that were highly expressed in the liver of the CGS (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis highlighted the importance of SRF in stomach protection. The activated transcription factor CEBPA regulates proteins related to metabolism and detoxification, especially cytochrome P450 26 , that were highly expressed in the liver of the CGS (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…For example, C/EBPα regulates transcription of human fructose-1,6-bisphosphatase ( FBP1 ) gene via binding to the two overlapping C/EBPα binding sites located at nucleotide -228/-208 ( Wattanavanitchakorn et al 2018 ), C/EBPα binding to the human polo-like kinase 1 ( PLK1 ) promoter results in suppressed PLK1 expression ( Dasgupta et al 2017 ). Furthermore, there were two C/EBPα binding sites in the chicken cytochrome P450 (CYP) 2D49 promoter, and over-expression of C/EBPα significantly upregulated CYP2D49 transcription ( Yang et al 2014 ). In this study, we identified that C/EBPα binds to the ACOX1 promoter region and suppressed its transcription activity.…”
Section: Discussionmentioning
confidence: 99%
“…Then, 59-biotin-labeled probes corresponding to putative NF-Y or Sp1 binding sites of porcine CYP3A29 and human CYP3A4 and CYP3A5 were prepared using an electrophoretic mobility shift assay (EMSA) Probe Biotin Labeling Kit (Beyotime). EMSA was performed with an EMSA Kit (Beyotime) according to a previously described method (Yang et al, 2014;Dong et al, 2015). Briefly, 5 mg nuclear extract protein from NF-YA/Sp1 overexpressed COS-7 or HepG2 cells were preincubated in binding buffer for 10 minutes at 20°C.…”
Section: Methodsmentioning
confidence: 99%